Preclinical Evaluation of White Led-Activated Non-porphyrinic Photosensitizer OR141 in 3D Tumor Spheroids and Mouse Skin Lesions - Doix, Bastien; Bastien, Estelle; Rambaud, Alix; Pinto, Adán; Louis, Caroline; Grégoire, Vincent; Riant, Olivier; Feron, Olivier (Frontiers in Oncology, 2018)
Photodynamic therapy (PDT) is used to treat malignancies and precancerous lesions. Near-infrared light delivered by lasers was thought for a while to be the most appropriate option to activate photosensitizers, mostly porphyrins, in the depth of the diseased tissues. More recently, however, several advantages including low cost and reduced adverse effects led to consider light emitting diodes (LED) and even daylight as an alternative to use PDT to treat accessible lesions. In this study we examined the capacity of OR141, a recently identified non-porphyrin photosensitizer (PS), to exert significant cytotoxic effects in various models of skin lesions and tumors upon white light activation. Using different cancer cell lines, we first identified LED lamp as a particularly suited source of light to maximize anti-proliferative effects of OR141. We then documented that OR141 diffusion and light penetration into tumor spheroids both reached thresholds compatible with the induction of cell death deep inside these 3D culture models. We further identified Arlasove as a clinically suitable solvent for OR141 that we documented by using Franz cells to support significant absorption of the PS through human skin. Finally, using topical but also systemic administration, we validated growth inhibitory effects of LED-activated OR141 in mouse skin tumor xenograft and precancerous lesions models. Altogether these results open clinical perspectives for the use of OR141 as an attractive PS to treat superficial skin malignant and non-malignant lesions using affordable LED lamp for photoactivation.